Communities of Practice as an Improvement Tool for Knowledge Sharing in a Multi-Cultural Learning Community - Sie, Bing; Aho, Anne Maria; Uden, Lorna (2014)
Knowledge sharing among students is important, especially when students are working in groups. In practice, however, this is not easy to achieve, especially in a multicultural environment. Knowledge sharing should be promoted to students who are learning about knowledge management. This paper describes our experience of teaching a knowledge management course for undergraduate students earning their Bachelor’s degrees at Seinäjoki University of Applied Sciences in Finland. The students participating in the course came from multicultural backgrounds. From our observations, we found there were many barriers to knowledge sharing among the students. It is our belief that Communities of Practice would help students to overcome these barriers and thus be better equipped to share knowledge. This paper is the introduction to an in-progress research proposal about how to apply Communities of Practice for knowledge sharing among students in a multicultural learning community.